Academic Integrity Policy and Support Provisions: : Are Ontario Colleges setting International Students up for Success? - Gibson, Steacy; Eamer, Allyson (Canadian Perspectives on Academic Integrity, 2025)
International students are critical to the academic, social and economic vitality of post-secondary institutions in Canada, yet, their retention can be challenging. When relations between host and home nations are strained, students are at risk of being required to return home, or of having their scholarships revoked. During the pandemic, international students, forced to study entirely online due to campus closures, were at risk of not having their visas renewed. Another challenge to international student retention is non-compliance with academic integrity policy. Non-compliance can result in penalties leading to dropouts and expulsion. Unlike other external challenges, ensuring compliance with academic integrity policy is entirely within institutional jurisdiction, yet Canadian colleges and universities assume varying degrees of responsibility in this regard. Using colleges in Ontario, Canada, as a case study, this paper explores the extent to which each of Ontario's 22 English-medium colleges provides its international students with ready access to intelligible academic integrity policy and pro-active training therewith. Using a mixed-methods approach, this research consists of content and document analysis, as well as descriptive statistics, to examine the academic integrity policy and support provisions (accessed online through Google searches) of each college. Colleges were ranked as exemplary, adequate or in need of improvement along a number of dimensions including acknowledging different cultural understandings and availability of translated material. Findings demonstrate that there is much more that colleges can do to support international students (upon whose tuition fees they are so dependent) in the area of understanding academic integrity compliance.